Some Bioactive Constitutents Of Gc-Ms Analysis Of Bulbophyllum Kaitense Rechib. Stem Estern Ghats Of India. - A.KALAIARASAN,; S.AHMED JOHN, (International Journal of Pharma and Bio Sciences, 2011)
The bioactive constituents present in stem parts of Bulbophyllum kaitense. Rechib belongs to the family Orchidaceae. Six compounds in ethanolic extract. were identified by gas chromato graphy (GC-MS).This analysis revealed that Bulbophyllum kaitense Rechib stems contain mainly n-Hexadecanoic acid (57.93%) a-bisabolol (6.99%) 2,4,5- Trihydroxypyrimidine (2.62%) .It is the first report of identification of bio active constituents from stem parts of Bulbophyllum kaitense Rechib by GC-MS